Estrategia de marketing digital para la gestión de la marca del licor Taita Waro en la cabecera parroquial de Guanujo, cantón Guaranda en el año 2024. - Urbina Ocampo, Rómulo Francisco (2025)
This research proposes a digital marketing strategy for launching and positioning the artisanal liquor brand "Taita Waro" in Guanujo parish, Guaranda canton, during the year 2024. Based on a quantitative approach, a survey was conducted with 346 participants, revealing strong community interest in locally produced goods and widespread use of social networks like Facebook and WhatsApp for information and recommendations. The proposed strategy integrates brand identity, storytelling, digital content, and loyalty actions, tailored to the rural and technological context of the region. The findings confirm that digital tools—when used with emotional and cultural focus—can strengthen the connection with local consumers and promote sustainable economic development.